Tutorial on Statistical Performance Evaluation Indices: A Review Study - Farzan Madadizadeh; Hooman Yekrang Safakar; Bita Forootani; Malihe Bolukyazdi; Zohreh Khosravani Shooli; Sajjad Bahariniya (Shahid Sadoughi University of Medical Sciences, 2023)
Statistical indicators are essential parts of research in many scientific fields such as health and treatment. These indicators play a major role in the evaluation of many health indicators in the general population and can help predict future issues. Statistical indicators are needed to evaluate performance of the tests. Two of the primary indicators are sensitivity and specificity, and other indices are obtained from them. In this tutorial study, evaluation indicators of statistical performance such as false negative rate (FNR), false positive rate (FPR), false discovery rate (FDR), false omission rate (FOR), bookmaker informedness (BM), markedness (MK), diagnostic odds ratio (DOR), positive likelihood ratio (PLR), negative likelihood ratio (NLR), prevalence threshold (PT), threat score (TS), prevalence (P), Fowlkes-mallows (FM), Phi-coefficient or Matthews correlation coefficient (MCC) and F1 score have been reviewed.